Increasing Number of Pancreas Transplantations in the Czech Republic. (July 2018) - Nemetova, Lenka; Girman, Peter; Jan, Kriz; Jindriska, Volkova; Dan, Holub; Neskudla, Tomas; Martina, Zahradnicka; Ema, Vavrova; David, Habart; Matej, Kocik; Kvetoslav, Lipar; Tomas, Marada; et al.
Abstract : Introduction: An effective programme of pancreas transplantations (simultaneous pancreas and kidney transplantation or as an isolated pancreas in non - uremic recipients) require a close cooperation of the transplant team with diabetes specialists and nephrologists from the referral area. While in many world –wide centers the transplant numbers trend to decline in recently years, the pancreas transplant programme in the Institute for clinical and experimental medicine has been rather growing approaching to the second – forth position in the world, according theInternational registry in organ donation and transplantation. Materials and Methods: We evaluate our recent effort to improve the overall advocacy of the pancreas transplant programme by organizing specialized presentations for practitioners, diabetologists, nephrologists and patients. We presented our outcomes, explain the indicated criteria and discuss with them. After two years, we analyze our results in the waiting list and compare data from between 2006 and 2016. Results and Discussion: Since 2006, we placed on the waiting list 306 recipients and we performed 329 pancreas transplantation: 284 pancreases and kidney transplantations and 45 isolated pancreas transplantations. Between 2006 and 2016 number of pancreas transplantations in our center increased from 25 in 2006 to 41 in 2016.Total new patients on waiting list increased from 19 in 2006 to 41 in 2016. Total time on waiting list dropped to 186, 5 days in 2016 (includethetotal numberof days on waiting list as an active or inactive candidate).Mean (±SD) BMI all active candidates was 24, 3±9, 6 kg/m2 in 2016. However, mean age all patients on waiting list increased from 40, 5 years in 2006 to 42, 2 years in 2016. The results showed significant increased number of candidates on waiting list and dropped total time on waiting list. Conclusions: Despite significant improved in diabetes care, still many patients with T1DM may profit from the pancreas transplantation.To make this process available for the most suitable recipients, long – term cooperation of the transplant team with referring specialists as well with diabetic patient group is very helpful. Supported by grant NV15-26746A of the Czech Republic